(untitled) (International Journal of Petroleum Technology, 2025)
The rising demand for diesel fuel amidst declining fossil reserves, volatile oil prices, and stringent emission regulations has driven the expansion of biodiesel production. Biodiesel, primarily produced as fatty acid alkyl esters via catalytic transesterification of triglycerides, offers advantages over fossil diesel, including environmental friendliness, non-toxicity, and enhanced lubricity. However, its limited oxidation stability, energy density, and cold flow properties restrict blending ratios with conventional diesel to prevent engine performance issues. Alternative methods, such as hydrotreated vegetable oils (HVOs), face challenges related to hydrogen dependency and cost. This review explores current biomass-derived diesel production methods and proposes a cost-effective strategy for industrial-scale biodiesel with improved stability, energy content, and cold flow characteristics. This approach aims to enable higher blending ratios with mineral diesel, reducing dependency on finite fossil resources while promoting cleaner, renewable energy use.